The Need for Blended Learning Development to Enhance the Critical Thinking of Thai Vocational Students - Wichian Deechai; Thanongsak Sovajassatakul; Sirirat Petsangsri (My University, 2019)
Abstract The objective of this research was to evaluate the need for blended learning development to enhance the critical thinking of students. Selected by using multistage random sampling, the 450 samples comprised of 376 vocational students and 69 teachers at vocational level. The research instrument used was a needs evaluation form, which was necessary to improve blended learning to enhance critical thinking. The index of consistency (IOC) was between 0.56-1.00, and the total reliability was 0.94. The research was conducted and data collected from July 2018 to August 2018. 445 completed evaluation forms, 98.88% of the total sent out, were returned to researchers. Frequency, percentage, PNI(Modified), and content analysis were used to analyze the data. The research results showed that the vocational students and teachers agreed on the same point that there should be development of student critical thinking skills. This development should comprise of critical thinking skills, learning achievement, and learning management. The recommendations made for improvement were to increase discipline within educational institutes, and to change and add facilities to support modern learning styles. Testing styles should be modern and correspond to student contexts. Moreover, learning styles should be improved to be up-to-date and to correspond to students’ needs and their real lives.
Keywords: Blended Learning; Learning Management; Education and Critical Thinking Development